ANALYSIS OF CRITICAL THINKING OF PROSPECTIVE MATHEMATICS TEACHERS IN SOLVING ASSESSMENT PROBLEMS - Sukriyah, Dewi; Juniati, Dwi (Universitas Sembilanbelas November Kolaka, 2023)
Simple qualitative descriptive research that describes the critical thinking skills of prospective mathematics teachers based on the percentage of achievement of critical thinking skills test results. we conducted research on 6th semester students of Mathematics Education Study Program consisting of 35 students. The research instrument used critical thinking skills test questions consisting of 5 questions prepared based on indicators of critical thinking skills consisting of identifying and interpreting, analyzing, evaluating, connecting, and solving problems. Data analysis used percentage. The results showed that the critical thinking skills of prospective mathematics teachers had a total average of 70% in the high category. This is supported by the percentage of critical thinking skills in each indicator as follows: interpreting and identifying indicators by 85%, analyzing indicators by 70%, connecting indicators by 82.14%, problem solving indicators by 20%, and evaluating indicators by 92.86%.